(untitled) (Scientific journal of the Fergana State University, 2026)
This article highlights the theoretical and practical foundations of forming and strengthening ideological immunity in the minds of young people. The article analyzes the essence of the concept of ideological immunity, socio-philosophical and spiritual-educational aspects of its upbringing. Also, the role of the family, educational institutions, and the mass media in ensuring the ideological stability of youth in the conditions of New Uzbekistan is shown on a scientific basis.